Charity law and the liberal state / Matthew Harding. - Harding, Matthew, 1974- (Cambridge University Press, 2014)
Charity Law and the Liberal State considers questions relating to state action and public discourse that are raised by the law of charity. Informed by liberal philosophical commitments and of interest to both charity lawyers and political philosophers, it addresses themes and topics such as: the justifiability of the state's non-neutral promotion of charitable purposes; the role of altruism in charity law; charity law, the tax system and the demands of distributive justice; the proper treatment of religious and political purposes in charity law; and the appropriate response of the liberal state to discrimination in the pursuit of charitable purposes.